Pengujian manfaat relasional dan kualitas hubungan sebagai anteseden loyalitas pelanggan - Rully Arlan Tjahyadi (Jurnal Manajemen Maranatha, 2020)
Customer-oriented business culture to be superior to competitors in fulfilling customer needs development (ie through learning) and respond with goods and services that deliver value to customers. The purpose of this study was to examine the effect of relational benefit and relationship quality on student loyalty. The object of research in this study is Maranatha Christian University. The unit of analysis in this study are individuals, such as students. The analysis used in this study is multiple regression with SPSS for Windows. Statistical analysis was used to examine the effect of relational benefit and relationship quality on student loyalty. Based on the results of processing using SPSS, relational benefit positive and significant impact on student loyalty. The same thing on the second hypothesis that relationship quality positive effect on student loyalty.